A framework to improve quality of hospital-based physiotherapy: a design-based research study - Rudi A. Steenbruggen; Marjo J. M. Maas; Thomas J. Hoogeboom; Paul L. P. Brand; Philip J. van der Wees (BMC, 2023)
Abstract Background A quality framework for hospital-based physiotherapy is lacking. This study aims to design a framework, building on the currently available literature, to improve the quality of hospital-based physiotherapy. Methods A multidisciplinary panel of six representatives of hospital-based physiotherapy and their key stakeholders (patients, medical specialists, hospital management and professional association) was set up. We used brainwriting to sample ideas and the 'decision-matrix' to select the best ideas. Results The first round of brainwriting with an online panel of six experienced participants yielded consensus on seven possible methods for quality improvement of hospital-based physiotherapy [1]: continuing education [2] ,feedback on patient reported experience measures and patient reported outcome measures [3] ,a quality portfolio [4] ,peer observation and feedback [5] ,360 degree feedback [6] ,a management information system, and [7] intervision with intercollegiate evaluation. Placing these methods in a decision matrix against four criteria (measurability, acceptability, impact, accessibility) resulted in a slight preference for a management information system, with almost equal preference for five other methods immediately thereafter. The least preference was given to a 360-degree feedback. Conclusions In the design of a framework for improving the quality of hospital-based physiotherapy, all seven suggested methods were perceived as relevant but differed in terms of advantages and disadvantages. This suggests that, within the framework, a mixture of these methods may be desirable to even out respective advantages and disadvantages.